2014
DOI: 10.1111/1462-2920.12490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the unicellular nitrogen‐fixing cyanobacteria UCYNA and its prymnesiophyte host

Abstract: Summary 21Symbiotic interactions between nitrogen-fixing prokaryotes and photosynthetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
260
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(284 citation statements)
references
References 59 publications
21
260
2
1
Order By: Relevance
“…This implies a potential role of phosphate limitation in the shift in diazotroph community composition. UCYN-A1 and γ-24774A11 both appear to be broadly distributed throughout low-nutrient marine waters (Thompson et al, 2014;Langlois et al, 2015), and it has been hypothesised that these taxa thrive in oligotrophic conditions (Church et al, 2008;Krupke et al, 2014). In line with our findings in the ATS and Coral Sea, Moisander et al (2014) recently demonstrated that γ-24774A11 was significantly negatively correlated to soluble reactive phosphorous in the western South Pacific.…”
Section: Arafura Sea Coral Seasupporting
confidence: 88%
See 1 more Smart Citation
“…This implies a potential role of phosphate limitation in the shift in diazotroph community composition. UCYN-A1 and γ-24774A11 both appear to be broadly distributed throughout low-nutrient marine waters (Thompson et al, 2014;Langlois et al, 2015), and it has been hypothesised that these taxa thrive in oligotrophic conditions (Church et al, 2008;Krupke et al, 2014). In line with our findings in the ATS and Coral Sea, Moisander et al (2014) recently demonstrated that γ-24774A11 was significantly negatively correlated to soluble reactive phosphorous in the western South Pacific.…”
Section: Arafura Sea Coral Seasupporting
confidence: 88%
“…It must be noted that amplicon sequencing approaches can only reconcile relative abundances and therefore do not allow for the absolute quantification of colonial versus singlecelled diazotrophs and that it is difficult to directly equate diazotroph communities to N 2 fixation activity. However, we identified a range of photoautotrophic, photoheterotrophic and heterotrophic bacteria that share high similarities in nifH sequences to those recovered from similar oceanic environments (for example, Langlois et al, 2005;Moisander et al, 2010;Bombar et al, 2013;Moisander et al, 2014;Thompson et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the cell size of the UCYN-A2 host in open ocean samples was 4-5 μm, clearly smaller than that described in coastal sites, about 7-10 μm (Hagino et al, 2013;Thompson et al, 2014). This is in agreement with a greater contribution of B. bigelowii reads in the 0.8-5 μm size fraction (as compared with the 5-20 μm fraction) in the Tara-Oceans metabarcoding data analyzed here, as well as of UCYN-A2 reads in the same smaller size fraction in metagenomic samples of the South Atlantic (Cornejo-Castillo et al, submitted).…”
Section: Discussionmentioning
confidence: 58%
“…Later, endosymbiotic UCYN-A was also discovered in B. bigelowii by transmission electron microscopic observations (Hagino et al, 2013). Phylogenetic analyses using the UCYN-A nitrogenase (nifH) gene revealed at least three distinct clades, UCYN-A1, -A2 and -A3 (Thompson et al, 2014), and highlighted specificity between host and symbiont pairings, suggesting co-evolution between symbionts and hosts Thompson et al, 2014). Thus the clade UCYN-A1 was associated with an open ocean small prymnesiophyte (hereafter UCYN-A1 host), and the clade UCYN-A2 was associated with the coastal and larger B. bigelowii (hereafter UCYN-A2 host), while no host has been yet proposed for UCYN-A3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation